Cell wall polymer distribution in bamboo visualized with in situ imaging FTIR. (15th November 2021) - Zhu, Jiawei; Wang, Hankun; Guo, Fei; Salmén, Lennart; Yu, Yan
Abstract: To better understand the high recalcitrance of bamboo during bioconversion, the fine spatial distribution of polymers in bamboo was studied with Imaging FTIR microscopy under both transmission and ATR modes, combined with PCA data processing. The results demonstrated that lignin, xylan and hydroxycinnamic acid (HCA) were more concentrated in the fibers near the xylem conduit, while cellulose was evenly distributed across the whole fiber sheath. PCA processing produced a clear separation between bamboo fibers and parenchyma cells, indicating that the parenchyma cells contains more pectin and HCA than fibers. It also demonstrated that cellulose, xylan and S-lignin were concentrated most heavily in bamboo fiber secondary cell walls, while G-lignin, pectin and HCA were found more in the compound middle lamella. The revealed information regarding polymer distribution is of great significance for better understanding of the inherent design mechanism of plant cell wall and its efficient utilization. Graphical abstract: Imaging FTIR with ATR first demonstrated that for bamboo, in similarity with wood species, the spatial distribution of cellulose, xylan and S-lignin were concentrated most heavily in the fiber secondary cell walls, while G-lignin, pectin and hydroxycinnamic acid (HCA) were found more in the compound middle lamella. At the tissue level, imaging FTIR with transmission mode first demonstrated that lignin, xylan and HCA were more concentrated in the fibers near xylem conduit, while cellulose was evenly distributed across the whole fiber sheath. Unlabelled Image Highlights: The polymers distribution in bamboo at both tissue and cellular scale was revealed with Imaging FITR Xylan and lignin were found to be more concentrated in the fibers near the xylem conduit in bamboo Cellulose, xylan and S-lignin were more concentrated in the secondary wall